PIGMENT CONTENT AND COMPOSITION IN AUTOTROPHIC AND HETEROTROPHIC LEAF TISSUES OF AMARANTH SPECIES A. TRICOLOR L. - M. S. Gins; V. F. Pivovarov; V. K. Gins; A. A. Baikov; S. Ju. Platonova; E. M. Gins (Овощи России, 2016)
At present there is numerous evidence of the antioxidant positive role in the defensive reaction that is capable to protect not only plants, but also humans against oxidative stress. Plant pigments such as natural dyes from leaves, flowers and fruits are known to have high antioxidant activity. Amaranth species A. tricolor L. cultivar ‘Early Splendor’ is a convenient model for the comparative studying of the formation processes of differently colored pigment composition in leaf tissues that differs in the ability to photosynthesize. Leaves of amaranth cultivar ‘Valentina’ were as a standard. The aim of the experiment was a comparative studying of the pigments content: amaranthine, chlorophyll a and b, carotenoids in the cauline leaves of amaranth cultivars ‘Valentina’ and ‘Early Splendor’, as well as in the red and green areas of the leaves. Analysis of the aqueous extract of red Early Splendor amaranth apical leaves showed the presence of betacyanin pigment - amaranthine, in the absorption spectrum in which peak was seen in the green region at 540 nm. In addition to the antioxidant amaranthine there are  also antioxidants which might be phenolic glycosides, and ascorbic acid in the extract, the total content of which is almost twice as small as in the leaves of amaranth cauline of this cultivar. Yellow fraction was found in the ethanolic extract of red leaves. Its absorption spectrum had peaks in the blue region at 445 nm and 472 nm and a shoulder at 422 nm that indicated the presence of betaxanthin, betalamic acid or carotenoids. Water-soluble antioxidants - amaranthine and ascorbic acid were found in  auline leaves of studied species. Their content in the leaves of Valentina cultivar was higher than in the leaves of cultivar ‘Early Splendor’, and the maximum level of photosynthetic pigments was found in ‘Early Splendor’ leaves. The obtained results showed that the amaranth is a promising source of pigments with the antioxidant  activity that can be used for production of food dyes.